2020
DOI: 10.1177/1010428320924524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating macrophage migration inhibitory factor 1 expression as a prognostic biomarker in colon cancer

Abstract: Objective: Several studies indicate that macrophage migration inhibitory factor 1 plays a role for tumor progression in colon cancer. We investigated whether determination of migration inhibitory factor 1 mRNA expression levels in lymph nodes of colon cancer patients could be used as a prognostic marker. Methods: Expression levels of migration inhibitory factor 1 and carcinoembryonic antigen mRNAs were assessed in primary tumors and regional lymph nodes of 123 colon cancer patients (stages I–IV), and in colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…We found that low levels of GPR55 mRNA was associated with poor prognosis. The finding contrasts with the results for all other biomarker mRNAs that we have studied so far, i.e., CEA, CXL17, CXCL16, LGR5, LGR4, GPR35V2/3 and EpCAM [10,[12][13][14][15][16][17], for which high levels were associated with poor prognosis. Notably, this reverse correlation was only found in lymph nodes.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that low levels of GPR55 mRNA was associated with poor prognosis. The finding contrasts with the results for all other biomarker mRNAs that we have studied so far, i.e., CEA, CXL17, CXCL16, LGR5, LGR4, GPR35V2/3 and EpCAM [10,[12][13][14][15][16][17], for which high levels were associated with poor prognosis. Notably, this reverse correlation was only found in lymph nodes.…”
Section: Discussioncontrasting
confidence: 99%
“…Afterwards, the sections were incubated with FITC-conjugated BerEP4 (green) (mouse IgG1, clone BerEP4, F0860; Dako). Double-positive cells show a yellow-orange color, as previously described [ 33 ]. Mouse IgG, ready to use (Dako) and FITC-conjugated anti-mouse (F0313; Dako) were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of MIF expression is dependent on the tumor tissue type, stage, and grade among other factors (10). For example, intratumoral MIF is increased-versus normal tissue-three-and five-fold in endometrial carcinoma and non-small cell lung carcinoma (11,12), respectively, ten times in hepatocellular carcinoma (13) and sixty times in colorectal cancer (14). In hepatocellular carcinoma, a positive correlation was also identified between intratumoral MIF and plasma MIF, suggesting that high tumor-associated MIF expression may drive higher circulating levels of soluble MIF (13).…”
Section: Mif's Mechanisms Of Actionmentioning
confidence: 99%